2010
DOI: 10.1111/j.1365-313x.2010.04393.x
|View full text |Cite
|
Sign up to set email alerts
|

APUM23, a nucleolar Puf domain protein, is involved in pre-ribosomal RNA processing and normal growth patterning in Arabidopsis

Abstract: SUMMARYPumilio, an RNA-binding protein that contains tandemly repeated Puf domains, is known to repress translational activity in early embryogenesis and polarized cells of non-plant species. Although Pumilio proteins have been characterized in many eukaryotes, their role in plants is unknown. In the present study, we characterized an Arabidopsis Pumilio-encoding gene, APUM23. APUM23 is constitutively expressed, with higher levels in metabolically active tissues, and its expression is up-regulated in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
149
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(175 citation statements)
references
References 70 publications
24
149
0
Order By: Relevance
“…These leaf developmental defects are reminiscent of the Arabidopsis mutants of ribosome proteins (40) (Table S1), like S18A (also known as POINTED FIRST LEAF, pfl in its mutant) in the small subunit (41), or L4A and L4D in the large subunit (42). Moreover, null mutants of many nucleolus-localized ribosome assembly factors (Table S1), including the Pumilio-like RNA binding protein ARABIDOPSIS PUMILIO 23 (APUM23) (24), nucleolar RNA helicase ARABIDOPSIS MRNA TRANSPORT 4 (AtMTR4) (23), and a putative methyltransferase ROOT INITI-ATION DEFECTIVE 2 (RID2) (43), also display similar developmental defects and aberrant pre-rRNA processing. In addition to the leaf phenotypes, atprmt3 mutants also displayed growth retardation, including delayed germination and primary root growth (Fig.…”
Section: Disruption Of Atprmt3 Confers Pleiotropic Developmental Defectsmentioning
confidence: 99%
See 3 more Smart Citations
“…These leaf developmental defects are reminiscent of the Arabidopsis mutants of ribosome proteins (40) (Table S1), like S18A (also known as POINTED FIRST LEAF, pfl in its mutant) in the small subunit (41), or L4A and L4D in the large subunit (42). Moreover, null mutants of many nucleolus-localized ribosome assembly factors (Table S1), including the Pumilio-like RNA binding protein ARABIDOPSIS PUMILIO 23 (APUM23) (24), nucleolar RNA helicase ARABIDOPSIS MRNA TRANSPORT 4 (AtMTR4) (23), and a putative methyltransferase ROOT INITI-ATION DEFECTIVE 2 (RID2) (43), also display similar developmental defects and aberrant pre-rRNA processing. In addition to the leaf phenotypes, atprmt3 mutants also displayed growth retardation, including delayed germination and primary root growth (Fig.…”
Section: Disruption Of Atprmt3 Confers Pleiotropic Developmental Defectsmentioning
confidence: 99%
“…Then we focused on atprmt3-2 and AtPRMT3-GUS for further Northern blot assays. We used apum23-1 as a control mutant, because it shows aberrant accumulation of 35S and polyadenylated P-A3 pre-rRNAs (24). Probes used previously (22,23) were able to detect the 35S and 33S precursors (Fig.…”
Section: Prmt3 Is Required For Proper Pre-rrna Processing In Arabidopmentioning
confidence: 99%
See 2 more Smart Citations
“…Any mutation in the ribosomal subunit genes affects auxin biosynthesis due to defective ribosomes, which translationally repress the auxin responsive factors, such cellular localization demonstrated that cytoplasmic punctuate structures are formed for many of the Arabidopsis Puf proteins, such as APUM7 (At1g78160), APUM8 (At1g22240), APUM9, APUM10, APUM12 (At5g56510), APUM14 (At5g43110) and APUM18. 44 However, others, i.e., APUM23 (At1g72320) and APUM24 (At3g16810), localize to the nucleolus, 44,45 suggesting that certain Puf proteins are involved in organelle-specific functions.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%